Predicting Levels of Policy Advocacy Engagement Among Acute-Care Health Professionals. (February 2016) - Jansson, Bruce S.; Nyamathi, Adeline; Heidemann, Gretchen; Bird, Melissa; Ward, Cathy Rogers; Brown-Saltzman, Katherine; Duan, Lei; Kaplan, Charles
This study aims to describe the factors that predict health professionals' engagement in policy advocacy. The researchers used a cross-sectional research design with a sample of 97 nurses, 94 social workers, and 104 medical residents from eight hospitals in Los Angeles. Bivariate correlations explored whether seven predictor scales were associated with health professionals' policy advocacy engagement and revealed that five of the eight factors were significantly associated with it ( p  < .05). The factors include patient advocacy engagement, eagerness, skills, tangible support, and organizational receptivity. Regression analysis examined whether the seven scales, when controlling for sociodemographic variables and hospital site, predicted levels of policy advocacy engagement. Results revealed that patient advocacy engagement ( p  < .001), eagerness ( p  < .001), skills ( p  < .01), tangible support ( p  < .01), perceived effectiveness ( p  < .05), and organizational receptivity ( p  < .05) all predicted health professional's policy advocacy engagement. Ethical commitment did not predict policy advocacy engagement. The model explained 36% of the variance in policy advocacy engagement. Limitations of the study and its implications for future research, practice, and policy are discussed.